2007
DOI: 10.1002/ijfe.348
|View full text |Cite
|
Sign up to set email alerts
|

FDI location choice: agglomeration vs institutions

Abstract: Using an extensive data set on foreign invested enterprises in China from US, EU, Japan and Korea, we explore the role of agglomeration economies (network externalities) and government institutions as well as other more traditional factors in determining the (regional) locational choice of foreign direct investment (FDI). Employing firm-level discrete choice model, we find that provinces with stronger public institutions and higher horizontal and vertical agglomerations tend to attract more foreign investments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 28 publications
2
59
0
1
Order By: Relevance
“…Regional governance mainly refers to various aspects of government institutions such as government intervention in the private sector, government protection of property rights, legal infrastructure and law enforcement (Du et al 2008). Regions with weak public institutions are typically characterized by heavy government intervention, inadequate protection of property rights and severe corruption, which may increase the expropriation risks to FDI.…”
Section: Regional Governancementioning
confidence: 99%
See 2 more Smart Citations
“…Regional governance mainly refers to various aspects of government institutions such as government intervention in the private sector, government protection of property rights, legal infrastructure and law enforcement (Du et al 2008). Regions with weak public institutions are typically characterized by heavy government intervention, inadequate protection of property rights and severe corruption, which may increase the expropriation risks to FDI.…”
Section: Regional Governancementioning
confidence: 99%
“…Studies confirm the impacts of regional governance on the location of foreign firms in China. For instance, Du et al (2008) found that less government intervention into business, better IPR protection and less corruption attract more foreign investments from the United States. To guarantee higher returns to capital, FDIRE would particularly favor those regions with supportive and conductive institutions.…”
Section: Regional Governancementioning
confidence: 99%
See 1 more Smart Citation
“…7 Consistent with this argument, Crozet et al (2004) and Du et al (2008) find that the tendency for foreign investors to cluster within a host country is strongest for investors from the same source country.…”
mentioning
confidence: 87%
“…Chakrabarti (2003) combined the theory of international trade under imperfect competition with the literature on the organizational strategy of multinationals to create a structural model that evaluates the role of several potential determinants on the spatial location of FDI. Du, Lu & Tao (2008), in turn, discussed the benefits of the agglomeration of firms as another important determinant of FDI, separating agglomeration into two types: vertical and horizontal. Vertical agglomeration refers to the existence of companies related to the production chain of the foreign capital enterprise (FCE), i.e., the existence of input suppliers, distributors and customers in the FCE sector.…”
Section: Literature Reviewmentioning
confidence: 99%